Tool support to aligning requirements and testing through behaviour-driven requirements patterns - Ribeiro, Pollyana de Queiroz; Veiga, Ernesto F.; Martins, Mariana C.; Vincenzi, Auri M. R.; Kudo, Taciana N.; Bulcão-Neto, Renato F. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20979, 2022)
The software industry still struggles with adverse effects of a weak alignment between requirements and testing. The Software Pattern Metamodel (SoPaMM) aligns requirements and test patterns under the influence of agile practices. However, these patterns will be more beneficial for professionals if development activities are supported by a software tool. This paper presents the behaviour-DRivEn Application Model generator (DREAM) tool, automatically generating requirements and test specifications from SoPaMM-based patterns. We show how DREAM supports requirements elicitation and specification, test case elaboration, and software documentation using a patterns catalogue for electronic health record systems.